(untitled) (Research, Society and Development, 2022)
In this article we address the process of preparing a pedagogical book with contemporary content in Astronomy. Our objective with this elaboration was to systematize a path that can serve as inspiration for other similar or close elaborations. This book can be used as a pedagogical resource for teachers of Science in Elementary Education. Some specific topics were chosen to structure this book, among which we highlight: phenomena observed on Earth and occurring in the Universe; use of units of astronomical measurements such as Light Year and Astronomical Unit (AU); conventions related to the notions of up and down. The book is organized in four chapters: Solar System, in which we characterize each of the bodies found in it; Eclipse, which guides the exploration of the phenomenon beyond what we have on our planet; Seasons, also considering the climate of the other planets in the Solar System; Storms, passing through the climate again, but relating Earth’s storms to those of other planets and ending with the greenhouse effect and global warming. This book was prepared considering data collected from the doubts about astronomy of graduates of Biological Sciences, Physics and Chemistry courses. In this book we also elaborated and applied ‘teaching modules’ addressing the shortcomings in the content pointed out by these students.